PERLINDUNGAN HUKUM TERHADAP SAKSI MAHKOTA DALAM PERKARA TINDAK PIDANA KORUPSI - Syamsuningsih, Sitti Nurhayati (Katalogis, 2016)
This research aims to find out and analyze urgency of legal protection for crown witness in crime and find out and analyze the form of protection given to crown witness in corruption, so the author raise problems as follow: (1) What is the urgency of legal protection for crown witness in crime?. (2) How is legal protection form for crown witness in corruption?. The research used juridical normative method with approach of Act, Conceptual and Case approach. The research results indicate that: (1) the urgency of legal protection for crown witness in crime is as witness status as the guilty actor and be ready to give true witness accused to him/her to complete evidences of crime examined. (2) the form of legal protection given to the crown witness in corruption can be given by reducing punishment and immune of demand that depending on judgment and policy of the judge.